Study on Flexural Strength and Flexural Failure Modes of Carbon Fiber/Epoxy Resin Composites - He, Hongwei; Li, Kaixi (Journal of Research Updates in Polymer Science, 2014)
The flexural failure modes and flexural strength of unidirectional carbon fiber/epoxy (CF/epoxy) composites was theoretically analyzed and calculated. The hypothesis that the maximal flexural strength of unidirectional CF/epoxy composites occurred in outer sheet layer was brought forward. Load-displacement curve of unidirectional CF/epoxy composites also demonstrates that it is correct, which is consistent with the assume. Unidirectional CF/epoxy composites were fabricated with winding and compression molding, and three different kinds of fiber packing modes were proposed and the effects of these modes on flexural prosperities of composites had also been analyzed respectively. Three failure modes, namely fracture of fiber, fracture of epoxy resin and interfacial delamination between fiber and matrix, were analyzed by scanning electron microscopy (SEM). The load-displacement curve of unidirectional CF/epoxy composites indicates the plastic deformation is increased with increasing phenolic resin.